The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1074/jbc.m109.035766
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori CagA Causes Mitotic Impairment and Induces Chromosomal Instability

Abstract: Infection with cagA-positive Helicobacter pylori is the strongest risk factor for the development of gastric carcinoma. The cagA gene product CagA, which is delivered into gastric epithelial cells, specifically binds to and aberrantly activates SHP-2 oncoprotein. CagA also interacts with and inhibits partitioningdefective 1 (PAR1)/MARK kinase, which phosphorylates microtubule-associated proteins to destabilize microtubules and thereby causes epithelial polarity defects. In light of the notion that microtubules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 48 publications
1
49
0
1
Order By: Relevance
“…Nonphosphorylated CagA associates with the epithelial tight junction scaffolding protein zonula occludens 1 (ZO-1) and the transmembrane protein junctional adhesion molecule A (JAM-A), leading to nascent but incomplete assembly of tight junctions at ectopic sites of bacterial attachment (13). Recently, CagA was shown to directly bind PAR1b/MARK2, a central regulator of cell polarity, and to inhibit its kinase activity as well as to dysregulate mitotic spindle formation, thus promoting a loss of cell polarity (see "Apical-Junctional Complexes") (179,269,320). While it is evident that non-tyrosine-phosphorylated mutant forms of CagA exert effects within gastric epithelial cells, to our knowledge, there is currently no direct evidence for nonphosphorylated CagA within the host cell.…”
Section: Vol 23 2010mentioning
confidence: 99%
“…Nonphosphorylated CagA associates with the epithelial tight junction scaffolding protein zonula occludens 1 (ZO-1) and the transmembrane protein junctional adhesion molecule A (JAM-A), leading to nascent but incomplete assembly of tight junctions at ectopic sites of bacterial attachment (13). Recently, CagA was shown to directly bind PAR1b/MARK2, a central regulator of cell polarity, and to inhibit its kinase activity as well as to dysregulate mitotic spindle formation, thus promoting a loss of cell polarity (see "Apical-Junctional Complexes") (179,269,320). While it is evident that non-tyrosine-phosphorylated mutant forms of CagA exert effects within gastric epithelial cells, to our knowledge, there is currently no direct evidence for nonphosphorylated CagA within the host cell.…”
Section: Vol 23 2010mentioning
confidence: 99%
“…It is interesting to note that although chronic gastritis appears to be associated with the development of gastric carcinoma in humans, there were no signs of gastritis or systemic in fl ammation in CagA transgenic mice, including those with gastrointestinal carcinomas. Interaction of CagA with PAR1/MARK (partitioning defective 1/ microtubule af fi nity-regulating kinase) may also contribute to the carcinogenic process because it induces chromosomal instability by destabilizing the microtubules during mitosis (Umeda et al 2009 ) .…”
Section: Helicobacter Pylori : An Inducer Of the Cpg Island Methylatomentioning
confidence: 99%
“…Indeed, mutation frequencies are more elevated in mice infected with H. pylori, with a prevalence of transversion mutations (AT to GC and GC to AT), resulting from oxidative DNA damage [14]. Umeda and co-workers showed that CagA, a virulence factor delivered into H. pylori-infected cells delays prophase and metaphase, resulting in the incorrect orientation of the mitotic spindle and an abnormal division axis, generating anomalies in chromosome segregation and genomic instability [15]. H. pylori also alters the level of the pro-apoptotic regulator p53 through the promotion of ubiquitin-dependent proteasome degradation in a CagA-dependent manner [16,17].…”
Section: Helicobacter Pylori Alters Content and Maintenance Of The Homentioning
confidence: 99%